Employees perception of good governance promotion in the public sector : case study at the state welfare department / Easter Michael Sutili @ Norhafizah - Michael Sutili, Easter @ Norhafizah (2011)
"Governance" and "good governance" which means the process of making decisions and decision processes implemented or not implemented. The department is the implementing agency for a ministry or the state administration. The department duties are under the objectives and policies of the ministry or the state administration, where it is placed. Good governance is particularly in the field of development assistance. Indeed, good governance is essential to the development process. The major contributors affecting to financial organizations increasingly targeted group and welfare aid on the condition that reforms and ensure "good governance" was conducted in administrative management. This study has an objective to identify weaknesses related to good governance and to evaluate the employees' perception of good promotion in the public sector at the State Welfare Department. This study is to suggest ways to promote good governance in the Department if there are any weaknesses identified during the findings and also to determine whether there is a significant, difference of perception across employees' age groups. The study has been conducted at the State Welfare Department.